2011
DOI: 10.2319/090310-518.1
|View full text |Cite
|
Sign up to set email alerts
|

Can we add chlorhexidine into glass ionomer cements for band cementation?

Abstract: Objective: To test if the addition of chlorhexidine digluconate (CHD) might influence the mechanical properties and antibacterial properties of two different conventional glass ionomer cements (GICs) used for band cementation. Materials and Methods: Two commercial brands of conventional GICs were used: Ketac Cem Easymix (3M/ESPE, St Paul, Minn) and Meron (Voco, Cuxhaven, Germany). The cements were manipulated in their original composition and also with 10% and 18% CHD in the liquid to create a total of six gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
38
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 24 publications
9
38
0
2
Order By: Relevance
“…With regard to the compressive strength, it was observed in the present study that different concentrations of CHX added to GIC did not change the results of the tests applied, thus corroborating studies conducted by Farret et al 23 . However, Türkün et al 3 observed GIC mixed with CHX at concentrations of 0.5% and 2% presented significant changes in the compressive strength.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…With regard to the compressive strength, it was observed in the present study that different concentrations of CHX added to GIC did not change the results of the tests applied, thus corroborating studies conducted by Farret et al 23 . However, Türkün et al 3 observed GIC mixed with CHX at concentrations of 0.5% and 2% presented significant changes in the compressive strength.…”
Section: Discussionsupporting
confidence: 80%
“…In order to improve the antibacterial properties of the GICs, the addition of CHX to this material has been tested and showed excellent results 3,10,17,23 . According to Palmer et al 5 ., GICs have the potential of slowly releasing active agents, such as fluoride 24 , and the CHX incorporated into GICS can be similarly released into the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diametral tensile strength results are pre- 16 found no statistical difference in DTS tests for Ketac Cem (7.41 MPa) and Meron (6.05 MPa) (both conventional glass ionomers). In our study, Meron was statistically superior to Ketac Cem for DTS, compared to resin modified glass ionomer cement (FJ), but was inferior to BL and MC statistically ( Table 2).…”
Section: Resultsmentioning
confidence: 85%
“…After insertion of the material, another Mylar strip was placed on the top surface followed by another glass slab pressed manually to obtain a regular surface. 16 After curing at the recommended time and without adding pressure, the specimens and the matrix were immersed in distilled water at 37°C for 15 minutes. The specimens were then ground and polished with 600 grit sand paper, and stored in water at 37°C for 24 hours.…”
Section: Flexural Strength Testmentioning
confidence: 99%